THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE: The Effect of Work Motivation and Work Discipline on Employee Performance - Hakim, Adi Lukman; Faizah, Erna Nur; Nujulah, Firdausi (Economic and Bussiness Faculty, Dr Soetomo University, 2021)
Human resources management is one that is needed in the era of globalization. Every organizational goal always expects resources that are able to work effectively and so that the company can be achieved. Human Resources is a central factor in an organization. The research objective is to determine the effect of work discipline and work motivation on employee performance at Kopitiam Cafe and Restaurant partially and simultaneously. Research method with associative method then using a quantitative descriptive approach. Multiple linear regression is a data analysis technique. The results of this study are as follows: The more disciplined an employee is in working, the more employee performance increases. The effect of these variables is significant positive . The more an employee is motivated to be enthusiastic about work, the more employee performance increases. The effect of these variables is significant positive. The more disciplined an employee is in working and the more motivated an employee is to be enthusiastic at work when combined simultaneously, the more employee performance increases. The effect of these variables is significant positive.